Construction of a Social Avoidance Scale for Football Players - Hassan, Omer Ali (Indonesian Journal Publisher, 2025)
The present study aims to constructing a reliable and valid scale to measure social avoidance for Premier League football players in the Kurdistan Region of Iraq. The descriptive approach was adopted using the survey method. The research population comprised 304 players representing 16 Premier League clubs, from which a sample of 181 players (59.53% of the population) was selected. An initial version of the scale was constructed and its validity was examined through both content validity and construct validity. Reliability was assessed using the split-half method, yielding a coefficient of 0.90, and Cronbach’s alpha, which was calculated at 0.88—both indicating high internal consistency. The final scale consists of three domains: Social Performance Avoidance (12 items), Social Interaction Avoidance (12 items), and Self-Disclosure Avoidance (10 items). The findings confirm that the Social Avoidance Scale possesses precise psychometric properties, making it suitable for accurately measuring this psychological construct. Based on the results, the study recommends periodic application of the scale to monitor this important psychological variable among football players.